2003
DOI: 10.1517/13543784.12.1.87
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potential of dipeptidyl peptidase IV inhibitors for the treatment of type 2 diabetes

Abstract: Incretins are peptide hormones, exemplified by glucose-dependent insulinotropic peptide and glucagon-like peptide 1 that are released from the gut in response to nutrient ingestion and enhance glucose-stimulated insulin secretion. Incretin action is terminated due to N-terminal cleavage of the peptides by the aminopeptidase dipeptidyl peptidase IV (DPP-IV). Hence, inhibition of glucose-dependent insulinotropic peptide and glucagon-like peptide 1 degradation via reduction of DPP-IV activity represents an innova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(57 citation statements)
references
References 138 publications
2
51
0
4
Order By: Relevance
“…Hence, one recent glucose-lowering strategic approach is to enhance active incretin hormone levels and activity through the development of selective DPP-IV inhibitors [6], [7]. The approach in both preclinical animal models of type 2 diabetes and in clinical studies of patients with type 2 diabetes has shown to increase levels of intact GLP-1 and GIP, ultimately leading to meaningful improvements in overall glucose homeostasis [8][10].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, one recent glucose-lowering strategic approach is to enhance active incretin hormone levels and activity through the development of selective DPP-IV inhibitors [6], [7]. The approach in both preclinical animal models of type 2 diabetes and in clinical studies of patients with type 2 diabetes has shown to increase levels of intact GLP-1 and GIP, ultimately leading to meaningful improvements in overall glucose homeostasis [8][10].…”
Section: Introductionmentioning
confidence: 99%
“…Another way to increase circulating GLP-1 is to inhibit the cleavage enzyme, DPP-4. In fact, DPP-4 inhibitors that raise endogenous concentrations of active GLP-1 [42] and have been shown to be effective in lowering fasting and postprandial glucose concentrations [43]. In contrast to GLP-1 based therapy, DPP-4 inhibitors have been shown to be weight neutral [5].…”
Section: Review Of Clinical Data On Glp-1 and Energy Homeostasismentioning
confidence: 99%
“…However, GLP-1 is degraded rapidly by the action of dipeptidyl peptidase 4 (DPP4; Kim et al, 2005a). Thus, stabilization of GLP-1 via DPP4 inhibition is a new therapeutic approach for type 2 diabetes (Drucker, 2003;Holst, 2004;Nielsen, 2005;Smalley et al, 2006). Sitagliptin is a first drug approved by FDA in 2006 as an inhibitor for DPP4.…”
Section: Research Articlementioning
confidence: 99%